O papel da família e do ensino religioso na formação ética do adolescente no ensino fundamental II, nas escolas estaduais de Boa Vista-Roraima - Morais, Maria Pinheiro (2015)
Studies focused on family, religion, school and teenagers has been the reason for concerns in several areas of social research, seeking to contribute to the scientific field and to society in general. The issue addressed in this paper develops the relationship between these issues, since the family in the society, the institutions and the school has a responsibility to contribute to the general education of adolescents and the students, and the religion contributes to the spiritual development of the human being through its religiosity. Each one seeking to develop its role, so that the main objective is to materialize as positive for society. Thus, this work proposes to research and identify the role of Family and Religious Education in adolescent ethics training in the Elementary School II, of the public schools of the city of Boa Vista - Roraima, focused on the transmission of values worked in the family and reinforced in school through the Religious Education discipline. In this sense it was carried out a field research and bibliographic, with qualitative and quantitative approach, exploratory, whose source of data collection and analysis, was a mixed questionnaire with open and closed questions, intended for students from public schools in Boa Vista-Roraima, where parents and guardians, collaborate with this work. The sample of the survey revealed that of the 198 students who took to the survey, 83 males and 115 females; 147 are in the age group up to 14 to 51 years are between the ages of 15 to 18 years old, all are attending school regularly. The participation of parents in the study was 167 people, 42 males and 125 females. As a result of the research, we can see the meeting of generations parents and children, are present through affective, where values strengthen family relationships. The big challenge is to practice, learn to use it often involves on the run, the activism of everyday reality is creating space, the values are being forgotten by both, and the relationship will fragmenting. Most students and parents agree that there is the discipline taught in school. The most compelling justifications are: knowledge, to respect other religion, work teaching values such as respect, to give value to others, help to have a balance between good and bad, to learn about religion and the knowledge of God, and to help to live in harmony to follow-up learning at home.